Addressing challenges in real-world image classification : long-tailed distribution and knowledge distillation - Wang, Yiming (Nanyang Technological University, 2022)
In computer vision, image classification has progressed rapidly with deep learning over the ten years. However, in the real world, we still face challenges to apply them when the datasets are highly imbalanced, or in some situations to deploy large networks.